2021
DOI: 10.1111/jgh.15680
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative bleeding and early death in percutaneous endoscopic gastrostomy: A multicenter retrospective study

Abstract: Background and Aim Comprehensive reports on the risk factors for bleeding and early death after percutaneous endoscopic gastrostomy (PEG) are limited. In this multicenter study, we retrospectively investigated the risk factors for bleeding and early death after PEG. Methods Patients (n = 1234) who underwent PEG between 2015 and 2020 at Osaka Medical and Pharmaceutical University and its affiliated hospitals (11 institutions in total) were evaluated for postoperative bleeding and early death (within 60 days) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another study, it was demonstrated that the combination of low albumin and high C-reactive protein levels predicted a high risk of early death after PEG (29). Multivariate regression analysis results of a comprehensive study of 1234 PEG implanted patients showed that low BMI, low serum albumin levels, and active cancer were independent risk factors for deaths occurring within 60 days (30). In another retrospective study, protein malnutrition, documented infection prior to the procedure, or cardiovascular disease were not found to be associated with mortality or complications (9).…”
Section: Resultsmentioning
confidence: 98%
“…In another study, it was demonstrated that the combination of low albumin and high C-reactive protein levels predicted a high risk of early death after PEG (29). Multivariate regression analysis results of a comprehensive study of 1234 PEG implanted patients showed that low BMI, low serum albumin levels, and active cancer were independent risk factors for deaths occurring within 60 days (30). In another retrospective study, protein malnutrition, documented infection prior to the procedure, or cardiovascular disease were not found to be associated with mortality or complications (9).…”
Section: Resultsmentioning
confidence: 98%
“… 9 Some studies have reported that the bleeding rate is high in the push method, includes procedures such as gastropexy or introducers on the abdomen. 10 However, a small-scale study comparing the pull and push methods in adults in Korea reported that there was no significant difference in infection or bleeding, and no buried bumper syndrome was reported. 11 Another study comparing outcomes between primary gastrostomy tubes and buttons (G-tube and G-button) in pediatric patients reported that primary G-tube offers no significant advantage in overall, minor or major complications when compared to primary G-button.…”
Section: Discussionmentioning
confidence: 99%